Major influence of CD4 count at the initiation of cART on viral and immunological reservoir constitution in HIV-1 infected patients. Issue 1 (December 2016) - Depincé-Berger, Anne-Emmanuelle; Vergnon-Miszczycha, Delphine; Girard, Alexandre; Frésard, Anne; Botelho-Nevers, Elisabeth; Lambert, Claude; Tedesco, Emilie; Genin, Christian; Pozzetto, Bruno; Lucht, Frédéric; Roblin, Xavier; Bourlet, Thomas; et al.
Abstract Background A persistent immune activation is observed in gut during HIV-1 infection, which is not completely reversed by a combined antiretroviral therapy (cART). The impact of the time of cART initiation may highly influence the size of the viral reservoir and theratio of CD4+ /CD8+ T cells in the gut. In this study, we analyzed the characteristics of HIV rectal reservoir of long-term treated patients, regarding their blood CD4+ T cells count at the time of cART initiation. Results Twenty-four consenting men were enrolled: 9 exhibiting a CD4+ T cells count >350/mm3 ("high-level CD4 group") and 15 < 350/mm3 ("low-level CD4 group") in blood, at the start of cART. An immunophenotypical analysis of T and B cells subpopulations was performed in blood and rectal biopsies. HIV cell-associated DNA loads and qualitative intra-cellular RNA were determined in both compartments. Theratio of CD4+ /CD8+ T cells was significantly decreased in the blood but not in the rectum of the "low-level CD4 group" of patients. The alteration in β7+ CD4+ T cells homing was higher in this group and was correlated to a lowratio of CD4+ /CD8+ T cells in blood. An initiation of cART in men exhibiting a low-level CD4 count was also associated with an alteration of B cells maturation. HIV blood and gut DNA reservoirs were significantly lower in the "high-level CD4 group" of men. A high HIV DNA level was associated to a detectable intracellular HIV RNA in rectum. Conclusions An early initiation of cART could significantly preserve gut immunity and limit the viral reservoir constitution.